Anthropometric factors related to sprint and agility performance in young male soccer players - Mathisen, G.; Pettersen, S. A. (Open Access Journal of Sports Medicine, 2015)
Objective: To investigate the relationship between anthropometrics and sprint and agility performance and describe the development of sprint (acceleration) and agility performance in 10- to 16-year-old male soccer players. Methods: One hundred and thirty-two participants were divided into three age groups, 10-12 years (mean 10.8±0.50), 13-14 years (mean 13.9±0.50), and 15-16 years (mean 15.5±0.24), with assessment of 20 m sprint with 10 m split time and agility performance related to body height and body mass within groups. Results: In the 10- to 12-year-olds, there were no significant correlations between height, weight, and the performance variables, except for body mass, which was correlated to 10-20 m sprint (r=0.30). In the 13- to 14-year-olds, body height was significantly correlated with 10 m sprint (r=0.50) and 20 m sprint (r=0.52), as well as 10-20 m sprint (r=0.50) and agility performance (r=0.28). In the 15- to 16-year-old group, body height was correlated to 20 m (r=0.38) and 10-20 m (r=0.45) sprint. Body mass was significantly correlated to 10 m spring (r=0.35) in the 13- to 14-year-olds, as well as 20 m (r=0.33) and 10-20 m (r=0.35) sprint in the 15- to 16-year-olds. Conclusion: Height and body mass were significantly correlated with sprint performance in 13- to 16-year-old male soccer players. However, the 10- to 12-year-olds showed no significant relationship between sprint performance and anthropometrics, except for a small correlation in 10-20 m sprint. This may be attributed to maturation, with large differences in body height and body mass due to different patterns in the growth spurt. The agility performance related to anthropometrics was insignificant apart from a moderate correlation in the 13- to 14-year-olds.